2022
DOI: 10.3389/fpls.2021.770363
|View full text |Cite
|
Sign up to set email alerts
|

Photocontrol of Axillary Bud Outgrowth by MicroRNAs: Current State-of-the-Art and Novel Perspectives Gained From the Rosebush Model

Abstract: Shoot branching is highly dependent on environmental factors. While many species show some light dependence for branching, the rosebush shows a strict requirement for light to allow branching, making this species an excellent model to further understand how light impinges on branching. Here, in the first part, we provide a review of the current understanding of how light may modulate the complex regulatory network of endogenous factors like hormones (SL, IAA, CK, GA, and ABA), nutrients (sugar and nitrogen), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 168 publications
0
0
0
Order By: Relevance
“…Thus, control of axillary bud formation and growth is important because axillary buds are needed or not needed depending on the use of the chrysanthemum. Numerous reports on genes or plant hormones involved in axillary bud formation and growth have been found in rice and Arabidopsis [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, control of axillary bud formation and growth is important because axillary buds are needed or not needed depending on the use of the chrysanthemum. Numerous reports on genes or plant hormones involved in axillary bud formation and growth have been found in rice and Arabidopsis [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In Arabidopsis, a variety of TFs have been identified as being critical for axillary bud formation and regulation, and the signaling hierarchy of each TF has been identified [3]. It has also been discovered that miRNAs regulate TFs necessary for axillary bud development [2]. Among the TFs that have been shown to be important for axillary bud formation in Arabidopsis, it has been reported that axillary bud formation is suppressed by the lateral suppressor-like gene [4] in an antisense transgenic chrysanthemum [5].…”
Section: Introductionmentioning
confidence: 99%